(untitled) (Revista de Artes Marciales Asiáticas, 2019)
This report describes the 6th European Judo Science & Research Symposium & 5th Scientific and Professional Conference - “Applicable Research in Judo,” held in Porec, Croatia, on June 12-14, 2019. The three-days conference included three keynote speakers on the first day which were followed by 12 presentations in two sections on the second day and a round table that closed the third and final day of the program. Proceedings book of the conference was published, which includes 17 papers. Although the conference organization was impeccable, the question remains how to further involve coaches in the conference and even more ignite their interest in science in judo to recognize the advantages that sports science could bring to their athletes and training processes.